The Influence of Top and Bottom Metal Electrodes on Ferroelectricity of Hafnia - Lee, Yongsun; Goh, Youngin; Hwang, Junghyeon; Das, Dipjyoti; Jeon, Sanghun (IEEE transactions on electron devices, 2021)
In recent years, several experimental approaches have been adopted to study and understand the mechanism and improve the ferroelectricity of fluorite-type hafnia-based ferroelectric materials. In this regard, significant efforts have been made to elucidate the role of top electrode and bottom electrode (TE and BE) materials in defining the ferroelectricity in such systems, especially in terms of induced mechanical tensile stress by these materials during the process of annealing. However, the effect of the electrode material was not investigated both at TE and BE, and despite numerous efforts, there is still a lack of accurate and systematic understanding. In this report, we have carried out a systematic investigation on the effect of TE and BE materials having different coefficient of thermal expansion (CTE), by changing the electrode material one at a time, both at the top and bottom. The influence of the TE was confirmed using [TE/Hf 0.5 Zr 0.5 O 2 (HZO)/TiN] structure in which the BE was fixed as TiN, and the influence of the BE was confirmed using [TiN/HZO/BE] structure by fixing TiN as the TE. As revealed by polarization versus electric field and residual stress analysis, smaller CTE of the electrode was found to result in higher tensile stress in the HZO films during the annealing process, facilitating the formation of higher ferroelectric o-phase and thereby resulting in greater ferroelectricity. Although the influence of TE and BE on the ferroelectric property of HZO films was found to show similar trends according to the CTE value of the electrodes, the influence of TE on the ferroelectric property of the HZO capacitors is found to be mainly due to the variation in the induced mechanical tensile stress; pulse switching measurement and X-ray photoelectron spectrometer (XPS) analysis suggest that in case of BE, both the induced mechanical tensile stress and the interfacial dead layer were found to play a significant part. As a result, BE was found to have a greater influence on ferroelectricity of the HZO capacitors when compared with that of TE. The highest remnant polarization of 48.2 and 58.7~μ \text{C} /cm 2 was obtained for W with the lowest of CTE of 4.5× 10^{-6}/^{° }\text{C} in both the configurations. The results obtained in this article are expected to provide a new way out to optimize the interface quality and ferroelectricity in HZO-based capacitors.